Mesa Verde - Shuter, Jane (Des Plaines, Ill. : Heinemann Library, 1999)
Discusses the cliff dwellings of Mesa Verde, Colorado, and what is known about the history, social life, and customs of the Ancestral Puebloans who lived in them.
Includes bibliographical references.
Keywords: Pueblo Indians -- Antiquities -- Juvenile literature; Pueblo Indians -- Social life and customs -- Juvenile literature; Cliff-dwellings -- Colorado -- Juvenile literature; Pueblo Indians; Indians of North America -- Colorado; National parks and reserves; Mesa Verde National Park (Colo.) -- Juvenile literature; Colorado -- Antiquities -- Juvenile literature; Mesa Verde National Park (Colo.); Colorado -- Antiquities